2003
DOI: 10.1074/jbc.m306881200
|View full text |Cite
|
Sign up to set email alerts
|

Phlorizin Recognition in a C-terminal Fragment of SGLT1 Studied by Tryptophan Scanning and Affinity Labeling

Abstract: SGLT1 as a sodium/glucose cotransporter is strongly inhibited by phlorizin, a phloretin 2-glucoside that has strong interactions with the C-terminal loop 13. We have examined phlorizin recognition by the protein by sitedirected single Trp scanning mutagenesis experiments. Six mutants (Q581W, E591W, R601W, D611W, E621W, and L630W) of truncated loop 13 (amino acids 564 -638) were expressed in Escherichia coli and purified to homogeneity. Changes in Trp quenching and positions of the emission maxima were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 23 publications
6
64
0
Order By: Relevance
“…In previous studies binding of the aglucone moiety of phlorizin could be shown to occur around aa 602 (ring B) and between aa 606 and aa 611 (ring A) (6). These interactions would bring the phlorizin molecule into a position where the glucose moiety points to a region downstream to the C terminus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies binding of the aglucone moiety of phlorizin could be shown to occur around aa 602 (ring B) and between aa 606 and aa 611 (ring A) (6). These interactions would bring the phlorizin molecule into a position where the glucose moiety points to a region downstream to the C terminus.…”
Section: Discussionmentioning
confidence: 99%
“…MALDI Mass Spectrometry-Mass spectra were acquired in the positive ion linear mode on a Voyager DE-PRO MALDI system (PE Biosystems) as described previously (6). Briefly, after mixing the solubilized protein with 2,5-dihydroxybenzoic acid matrix (saturated 2,5-dihydroxybenzoic acid solution in 0.1% trifluoroacetic acid and 50% acetonitrile), 0.5-l aliquots of the mixture were dispensed onto the sample support followed by 0.5 l of ␣-cyano-4-hydroxycinnamic acid matrix solution (solution of ␣-cyano-4-hydroxycinnamic acid in 0.1% trifluoroacetic acid and 50% acetonitrile).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phloridzin is a competitive inhibitor of SGLT1 that acts in a twostep process. Initially, instead of glucose binding, phloridzin binds with SGLT1, followed by a slow isomerization that results in phloridzin bound to the receptor-site of the SGLT (Raja et al, 2003). With phloridzin blocking the receptor, glucose cannot bind to the symporter and uptake is blocked on the apical side of the intestinal cell (Zheng et al, 2012).…”
Section: Figurementioning
confidence: 99%
“…To this end various methods have been used such as kinetic studies (7), electrophysiology methods (8), tryptophan scanning studies (9,10), mutagenesis studies (11,12), x-ray crystallography (13), and plasmon resonance spectroscopy (14) to name a few. Crystallographic data are available for Vibrio parahemeolyticus sodium/galactose symporter (vSGLT) (13) in the sodium-and galactose-bound state.…”
mentioning
confidence: 99%